Sounds of silence : an anti-realist perspective on YHWH's ipsissima verba in the Old Testament - Gericke, Jaco (Old Testament essays, 2005)
In the Old Testament one frequently encounters expressions like 'God said ...', 'Thus says YHWH ...' and so on. In these phrases it seems to be implied that what follows is a record of actual divine verbal communi-cation. But did a god named YHWH / God really speak to humans? In this article the author argues that the nature, history and contents of the supposed divine ipsissima verba appear to suggest that no deity actually uttered such discourse. When YHWH is depicted as speaking in the first person he is simply a character in a text and his words are demonstrably nothing more than all-too-human literary constructions. This conclusion suggests that we should rethink the way we understand the nature of reli-gious language, revelation and religious experience in the Old Testament.